The king's curse [compact disc, unabridged] - Gregory, Philippa (Gregory, Philippa. Cousins' war., 2014)
Margaret has to choose whether her allegiance is to the increasingly tyrannical king, or to her beloved queen; to the religion she loves or the theology which serves the new masters. Caught between the old world and the new, Margaret Pole has to find her own way as she carries the knowledge of an old curse on all the Tudors.